Sistem Pengawasan Kinerja Jaringan Server Web Apache dengan Log Management System ELK (Elasticsearch, Logstash, Kibana) - Tarigan, Claudia; Engel, Ventje Jeremias Lewi; Angela, Dina (Yayasan Petra Harapan Bangsa, 2018)
A server is a software that has a duty and responsibility to provide information to the web. Any process that occurs within the web server will be recorded in a log. A log is a file that contains a list of actions, events (activities) that have been going on in a computer system. By using the log files on a web server, a lot of things that can be done by system administrators to monitor the performance of the web server. However, the log on the web server are difficult to understand and read. Log management system is a system that can handle data services log in large numbers and generate detailed log information. Logstash is the application log management system that can help the system administrator in the performance monitor log of the web server. Logstash will be combined with the Elasticsearch serves as data storage media and Kibana as visualization. ELK (Elasticsearch, Logstash, Kibana) is used to display and keep an eye on the log data from web server so, system administrators can know the performance of the web server.Server sebagai penyedia layanan di jaringan memastikan agar semua aktivitas yang berkaitan dengannya dicatat dalam log. Log adalah file yang berisi daftar aktivitas dan waktu yang terjadi dalam server. Pemantauan kinerja server dengan memanfaatkan log akan meningkatkan ketahanan dan tingkat layanan sebuah server. Masalahnya adalah log yang tercatat tersebar di beberapa tempat dan susah untuk langsung diolah karena bentuknya bukan seperti tabel. Log management system dapat menangani data log dalam jumlah besar, menghasilkan detail informasi aktivitas, dan visualisasi data log yang lebih mudah dimengerti pengguna. Perangkat lunak ELK (Elasticsearch, Logstash, Kibana) bisa dikombinasikan dan diintegrasikan dalam server web untuk mengelola, manampilkan, dan mengawasi data-data log yang ada sehingga administrator jaringan dapat mengetahui kinerja yang terdapat pada server web. Implementasi dan uji coba menunjukkan pengawasan kinerja server web Apache yang lebih mudah dimengerti pengguna.